Strategic Plan for Archaeological Survey of Installations of the 611th Air Support Group Alaska - Argonne National Laboratory (1998)
This plan presents a strategy for archaeological inventory of the remote installations of the 611th Air Support Group (611 ASG), Eleventh Air Force, Pacific Air Forces. The remote installations of the 611 ASG are widely distributed across Alaska, and vary significantly in terms of size and geographic setting. The distribution and design of these installations, which include radar stations, communications sites, and fighter-interceptor bases, reflects their historic Cold War role in the strategic air defense of North America. In order to satisfy requirements of Section 110 of the National Historic Preservation Act (NHPA) for the identification of properties eligible for the National Register of Historic Places, the 611 ASG plans to conduct a comprehensive inventory of archaeological remains on these installations. A total of 29 installations are addressed in the plan.